Selection of cooking banana genotypes for yield and black Sigatoka resistance in different locations in Uganda - Tumuhimbise, Robooni; Buregyeya, H.; Barekye, A.; Ssali, R.T.; Talengera, D.; Kubiriba, Jerome; Muhangi, S.; Namagembe, B.; Namanya, P.; Arinaitwe, G.; Tushemereirwe, Wilberforce K.; Karamura, D.; et al. (Academic Journals, 2016)
It is imperative to systematically evaluate new banana genotypes in different locations before national release. This enables selection and recommendation of superior genotypes as new varieties for a wider range of environments. The objective of the present study was to select banana genotypes with stable and high performance for bunch yield and leaf black Sigatoka resistance. Eleven cooking banana genotypes developed by the Uganda National Agricultural Research Organization in collaboration with Bioversity International, and two check varieties were evaluated in multi-location preliminary yield trials in Uganda. Data collected were analyzed using Additive Main Effects and Multiplicative Interaction (AMMI) model, AMMI Stability Value, and Genotype Selection Index (GSI). Genotype × location interaction was significant for all the traits assessed. Most of the new genotypes had low interaction effects with locations for bunch yield (69.2%) and black Sigatoka (92.3%). The most stable genotypes for bunch yield were NABIO815, NABIO1117, NABIO216 and NABIO306 whereas for black Sigatoka resistance, were NABIO1011, NABIO815, NABIO1009 and NABIO216. Using the GSI that defines the most desirable genotypes as those that combine high agronomic performance and stability across environments, four genotypes (NABIO306, NABIO1011, NABIO808 and NABIO1009) were selected. These genotypes, in addition to their high performance for agronomic traits and stability, had soft and yellow fruit pulp on cooking, and will be advanced on farm for further evaluation